Progress on a European platform for applied territorial science. Third ESPON 2013 scientific report. December 2014. - (:unkn) unknown (My University, 2014)
Das ESPON 2013-Programm dient der Unterstützung der europäischen Regionalpolitik durch Studien, Daten und Beobachtung von Raumentwicklungstrends. Es kooperieren die 27 EU-Mitgliedstaaten sowie die Nachbarstaaten Island, Liechtenstein, Norwegen und die Schweiz.

This third ESPON 2013 Scientific Report presents achievements and developments to territorial sciences made in the 2013 Programme. It documents the progress made on building a scientific platform by refining and further developing methodologies, and it provides a valuable reference for further applied research action in the field of European territorial development. This Report presents the "use of ESPON", the most novel and innovative methods for applied sciences. This ranges from new developments related to European-wide comparable indicators on territorial developments, via quantitative and qualitative approaches to analysing recent territorial developments as well as possible future perspectives to practical territorial analysis tools that have been developed within the framework of the ESPON 2013 Programme.
Keywords: Raumwissenschaft; Regionalwissenschaft; Raumplanung; Regionalplanung; Raumentwicklung; Raumordnungspolitik; Planungsinstrument